The history of English spelling - Upward, Christopher; Davidson, George (Malden, Mass. : Wiley-Blackwell, 2011)
The History of English Spelling reveals the history of Modern English spelling, tracing its origins and development from Old English up to the present day. Includes a wealth of information and data on English spelling not available anywhere else. Includes detailed coverage of the contributions from French, Latin, Greek - and the many other languages - to our current orthography. Serves as a companion volume to Geoffrey Hughes's A History of English Words in the same series.
Introduction and overview -- England and English from the Romans to the Vikings -- The Old English roots of modern English spelling -- The decline and revival of English in the Middle English period -- The Franco-Latin element -- Some sound and spelling developments in middle and modern English -- The Greek contribution -- The exotic input -- Reformers, lexicographers and the parting of the ways.
Includes bibliographical references and index.
Print version record.
Keywords: English language -- Orthography and spelling -- History; English language -- Etymology; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Phonetics & Phonology; English language -- Etymology; English language -- Orthography and spelling; Electronic books; History